Differential distribution shifts in two subregions of East Asian subtropical evergreen broadleaved forests—a case of Magnoliaceae - Wu, Hai-Yang; Liu, Yue-Han; He, Qiu-Xiang; Ye, Jun-Wei; Tian, Bin (Frontiers in Plant Science, 2024)
Aim East Asian subtropical evergreen broadleaved forests (EBLFs) are composed of western and eastern subregions with different topographical and environmental conditions. The distribution shifts through time of plants in the two subregions are predicted to be different while the difference have seldom been investigated. Methods Potential distributions of 53 Magnoliaceae species (22 in western and 31 in eastern subregion) during last glacial maximum (LGM), present, and 2070s were predicted in MaxEnt based on 58 environmental variables. Changes of distribution range size and centroid through time were analyzed. Species-level potential habitat were overlaid to uncover species diversity distribution and the distributions through times were overlaid to discover long-term refugia. Results At present, potential distributions are much larger than that shown by the occurrence points. During the LGM, 20/22 species in western subregion experience increases in range size through downwards and southwards migrations, while decreases of range size in eastern subregion (27/31 species) are accompanied by northward and eastward migrations. In the future, range size declines and northward shifts are both found, northwestward shifts exist in most (20/22 species) species in western subregion while both northwest- and northeastward shifts occur in eastern subregion. The diversity hotspots experience slightly southward shift in the past and upwards to mountain region in the future in western subregion, and in eastern subregion, shrinks occur in eastern China in the past and shrinks are shown in all regions in future. Long-term refugia preserving diversity are found in mountains across the entire EBLFs region. Main conclusions Significant differences of distribution shifts from past to present, while similar distribution shifts from present to future are revealed in the two subregions. Species diversity in both subregions experience no significant shifts from past to future and the Magnoliaceae plants can be preserved in mountains region throughout the EBLFs.